Energy - Way, Steve; Bailey, Gerry (Pleasantville, NY : Gareth Stevens Pub., 2009)
Photographs, illustrations, and simple text describe different forms of energy, such as animal, wind, solar, electrical, and nuclear power.
What is energy? -- Pushing and pulling -- Human power -- Animal power -- Wind power -- Water power -- Solar power -- Burning power -- Turning power -- Electrical power -- Magnetic power -- Nuclear power -- Energy quiz -- Glossary.
Includes index.
5.7
3-6
Keywords: Power resources -- Juvenile literature; Power resources; Energy resources; Power resources; Energy